Frequency of Insulin Resistance and Their Association with BMI in Polycyclic Ovarian Syndrome - Seher Obaid, Shair Zaman Khan, Iftikhar Ali Kakar, Susan Kakakhel (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Polycystic Ovary Syndrome (PCOS) is among the most prevalent endocrine conditions that affects women of reproductive age. Genetics, obesity, birth weight and insulin resistance are some of the inherited and environmental variables that have been associated to the etiology of PCOS. Objective: To study the frequency of insulin resistance and their association with BMI in polycyclic ovarian syndrome Methods: This study was cross-sectional, carried out at the physiology department Northwest School of Medicine Peshawar. The study duration was six months from January 2022 to June 2022. After an overnight fast (12–14 hours), 2.5ml of venous blood was drawn into a sodium fluoride and EDTA tube. This blood was used to measure the fasting plasma glucose (FPG). Insulin levels were determined by concurrently drawing 2.5 ml of venous blood. A separate proforma was used to input all the data. On SPSS 23, all data were entered and examined. Results: In our study, totally 180 patients participated. The mean age with ±SD was 26±4.23 years. The overall frequency of insulin resistance observed in our study was 117 (65%). A statistical significant association was observed between BMI of ≥25 and insulin resistance (p=0.021). Conclusions: Our study concludes that the frequency of insulin resistance in polycyclic ovarian syndrome is high. A statistical significant association was observed between BMI of ≥25 and insulin resistance in our study. Keywords: Insulin resistance; BMI, polycyclic ovarian syndrome